2021
DOI: 10.3389/frvir.2021.627194
|View full text |Cite
|
Sign up to set email alerts
|

Behavioral Framework of Immersive Technologies (BehaveFIT): How and Why Virtual Reality can Support Behavioral Change Processes

Abstract: The design and evaluation of assisting technologies to support behavior change processes have become an essential topic within the field of human-computer interaction research in general and the field of immersive intervention technologies in particular. The mechanisms and success of behavior change techniques and interventions are broadly investigated in the field of psychology. However, it is not always easy to adapt these psychological findings to the context of immersive technologies. The lack of theoretic… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

1
37
0
4

Year Published

2021
2021
2024
2024

Publication Types

Select...
5
1
1

Relationship

2
5

Authors

Journals

citations
Cited by 46 publications
(42 citation statements)
references
References 52 publications
1
37
0
4
Order By: Relevance
“…Treatments for body image disturbances mainly rely on cognitive-behavioral therapy, typically combining psychoeducation and self-monitoring tasks, mirror exposure, or video feedback (Farrell et al, 2006;Ziser et al, 2018;Griffen et al, 2018). Based on the fundamentals of these established methods, an increasing number of researchers have started to explore VR applications as additional support for attitude and behavior change in general (Wienrich et al, 2021) and therapy of body image disturbance (Riva, 1997;Ferrer-Garcia et al, 2009Riva et al, 2019;Turbyne et al, 2021) and obesity in particular (Horne et al, 2020;Döllinger et al, 2019).…”
Section: Related Workmentioning
confidence: 99%
See 1 more Smart Citation
“…Treatments for body image disturbances mainly rely on cognitive-behavioral therapy, typically combining psychoeducation and self-monitoring tasks, mirror exposure, or video feedback (Farrell et al, 2006;Ziser et al, 2018;Griffen et al, 2018). Based on the fundamentals of these established methods, an increasing number of researchers have started to explore VR applications as additional support for attitude and behavior change in general (Wienrich et al, 2021) and therapy of body image disturbance (Riva, 1997;Ferrer-Garcia et al, 2009Riva et al, 2019;Turbyne et al, 2021) and obesity in particular (Horne et al, 2020;Döllinger et al, 2019).…”
Section: Related Workmentioning
confidence: 99%
“…These methods often use 3D models of human beings (Horne et al, 2020;Turbyne et al, 2021), which can be called avatar as they represent a particular user (Bailenson and Blascovich, 2004). VR in general, and the confrontation with avatars in particular, have great potential to influence human perception and behavior (Wienrich et al, 2021). Especially the feeling of embodiment towards an avatar holds enormous potential for therapeutic purposes (Matamala-Gomez et al, 2021).…”
Section: Introductionmentioning
confidence: 99%
“…Recent results show the Proteus effect caused by self-avatars also applies to the digital counterparts (the avatars) of others. Others demonstrated how XR potentials are linked to psychological variables (Wienrich and Gramlich, 2020;Wienrich et al, 2021a).…”
Section: Xr As a New Testbed For Human-ai Interactions And Interfacesmentioning
confidence: 99%
“…Results stemming from human-human interactions have shown that XR provides high ecological validity and high standardization for investigating social interactions between humans (Blascovich et al, 2002;Bombari et al, 2015;Pan and Hamilton, 2018;Wienrich and Gramlich, 2020;Wienrich et al, 2021a). AI applications, becoming increasingly interactive and embodied, lead up to essential changes from an HCI perspective and challenges of a valid and systematic investigability.…”
Section: Contribution 2: a New Testbed For Human-artificial Intelligence Interactions And Interfacementioning
confidence: 99%
See 1 more Smart Citation